Evaluation of generation reliability indices : the case of Taiwan Power Company - Chen, Chun-yao Jennifer; Oudheusden, Dirk L. van; Codoni, Rene; Awate, Prakash G.; Government of Rep. of China (Bangkok : Asian Institute of Technology, 1987)
The method of calculating generation reliability indices had been developed for over three decades; however, the accuracy of its estimation is still doubtful. This study used the historical record of Taiwan Power Company as a data base to estimate the generation reliability indices as if we did not know the records and then use the result to compared with the actual records in order to evaluate the generation reliability indices method . A computer program with eight sub routines was developed in this thesis study according to the developed theorem and a new load shape approximation method. Monthly load duration curves for each year were estimated and transferred into weekly load duration curves. After this, forced outage rate s of units were convolved with the approximated load duration curve to yield an equivalent load curve of customer' s demand by weekly intervals. Hydro energy were then shaved from the equivalent load duration curve according to two policies, namely economic water policy and defensive water policy, c hose n by the cases. At last, generation reliability indices Hourly Loss Of Load Expectation & Expected Energy Not Served) were calculated after hydro output was considered. Eight cases of different assumptions were calculated in the study a nd compared with the actual records. It shows that this method have better estimations when the reserved margin of the system is higher than 1 5%. Therefore , it is still a useful tool for the planning of future power expansion program.
A thesis report submitted in partial fulfillment of t he requirements for the degree of Master of Engineering, School of Engineering and Technology
Thesis (M.Eng.) - Asian Institute of Technology, 1987
Keywords: Electric power production -- Taiwan